A Plains‐wanderer (Pedionomidae) that did not wander plains: a new species from the Oligocene of South Australia. (3rd November 2014) - De Pietri, Vanesa L.; Camens, Aaron B.; Worthy, Trevor H.; Collinson, Martin
<x xml:space="preserve">Abstract</x> The remarkable fauna of Australia evolved in isolation from other landmasses for millions of years, yet understanding the evolutionary history of endemic avian lineages on the continent is confounded by the ability of birds to disperse over geographical barriers even after vicariance events. The Plains‐wanderer Pedionomus torquatus (Charadriiformes) is an enigmatic, predominantly sedentary, quail‐like bird that occurs exclusively in sparse native grasslands of southeastern Australia. It is the only known species of its family (Pedionomidae), and its closest relatives are the South American seedsnipes (Thinocoridae). Here we describe a further representative of this lineage, Oligonomus milleri gen. et sp. nov., from the Late Oligocene of South Australia (26–24 Ma), which pre‐dates the earliest record of P. torquatus by c. 22 Ma and attests to the presence of this lineage during Australia's period of isolation (50–15 Ma). Based on the morphology of the coracoid and the palynological record, we propose that O. milleri and P. torquatus were ecologically disparate taxa and that, similar to coeval marsupials, O. milleri inhabited well‐wooded habitats, suggesting that the preference for grassland in the extant P. torquatus and thinocorids is likely to be convergent and not ancestral. The speciation event leading to the evolution of the extant Plains‐wanderer was probably triggered by the spread of grasslands across Australia in the Late Miocene–Pliocene, which this record pre‐dates. The presence of a pedionomid in the Late Oligocene of Australia strengthens the hypothesis of a Gondwanan divergence of the lineages giving rise to Thinocoridae and Pedionomidae.